Covid Adult Mortality in Brazil: An Analysis of Multiple Causes of Death - Nogales Vasconcelos, Ana Maria; Ishitani, Lenice; Abreu, Daisy Maria Xavier; França, Elisabeth (Frontiers in Public Health, 2022)
Objective: This study aimed to analyze the chain of events and contributing causes associated with COVID-19 adult mortality (30-69 years old), based on qualified data on CoD from three Brazilian capitals cities, Belo Horizonte, Salvador, and Natal, in 2020. Methods: Data of all deaths among residents in the three capitals in 2020 were provided by these municipalities' routine Mortality Information System (SIM). Mentions B34.2 with the markers U07.1 and U07.2 in the death certificate identified COVID-19 deaths. We used a multiple-cause-of-death approach better to understand the complexity of the morbid process of COVID-19. Conditions that appeared more frequently in the same line or above the COVID-19 mentions in the death certificate were considered a chain-of-event. Conditions that occurred more often after the codes for COVID-19 were considered as contributing. Results: In 2020, 7029 records from COVID-19 as the underlying cause of death were registered in SIM in the three capitals. Among these, 2921(41.6%) were deceased between 30 and 69 years old, representing 17.0% of deaths in this age group. As chain-of-events, the most frequent conditions mentioned were sepsis (33.4%), SARS (32.0%), acute respiratory failure (31.9%), unspecified lower respiratory infections (unspecified pneumonia) (20.1%), and other specified respiratory disorders (14.1%). Hypertension (33,3%), diabetes unspecified type (21.7%), renal failure (12.7%), obesity (9.8%), other chronic kidney diseases (4.9%), and diabetes mellitus type 2 (4.7%) were the most frequent contributing conditions. On average, 3.04 conditions were mentioned in the death certificate besides COVID-19. This average varied according to age, place of death, and capital. Conclusion: The multiple-cause analysis is a powerful tool to better understand the morbid process due to Covid-19 and highlight the importance of chronic non-communicable diseases as contributing conditions.